Pencirian titanium berbusa yang dihasilkan pada suhu pensinteran yang berbeza menggunakan kaedah buburan - S. Ahmad,; N. Muhamad,; A. Muchtar,; J. Sahari,; K.R Jamaludin,; M.H.I. Ibrahim,; N.H. Mohamad Nor,; Murtadhahadi, (Penerbit Universiti Kebangsaan Malaysia, 2010)
The mechanical and physical propertics of titanium foam sintered at different temperatures are reported in this paper. In this work, the slurry method has been used for the production of titanium foams using pure titanium and titanium alloy (Ti6Al4V). The titanium slurry was first prepared by mixing the titanium powder, polyethylene glycol (PEG), methylcellulose and water. Polyurethane (PU) foams, which acted as scaffolds were then impregnated in the slurry, followed by drying at room temperature. These were later sintered in a high temperature vacuum furnace at 1200oC, 1250oC and 1300¡C. The resultant titanium foams were characterised using Scanning Electron Microscopy (SEM) and the compressive strength test. The range of pore sizes obtained was between 388 μm to 1.07 mm, with a strut size in the range of 59.4 μm to 227 μm. The highest compressive strength obtained was 14.85 MPa. This was for the titanium alloy foam which had been sintered at 1250¡C. The highest density (1.25 g/cm3) obtained was for the pure titanium foams that were sintered at 1300¡C. For these, the porosity was found to be 65.05%. In general however, the most suitable sintering temperature was found to be 1250¡C for both the pure titanium and titanium alloy.